2021
DOI: 10.3390/en14071916
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of the Normative Calculation Method of the Exhaust Emissions and Fuel Consumption in the Vehicles Fueled with Gaseous Fuels

Abstract: The methodologies for calculating exhaust emissions and fuel consumption, which are given in the normative documents, do not take into account the fact that vehicles equipped with liquefied petroleum gas (LPG) or compressed natural gas (CNG) systems are fueled with petrol after a cold start. When calculating exhaust emissions and fuel consumption of LPG or CNG-powered vehicles, it is assumed that they result from the combustion of gaseous fuel only. This simplification leads to an incorrect determination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Grzelak et al [33] (2021) indicated that the use of various calculation methods may result in approximately 7% underestimation of road CO 2 emission results when testing LPG-powered vehicles. This was also confirmed by Gis et al [34] (2021), indicating that the interchangeable treatment of indicators (dilution ratio and dilution factor) in mathematical calculations of exhaust emissions affected the measurement error of CO 2 concentration by 0.4%, CO by a maximum of 4%, and NO x by 1%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Grzelak et al [33] (2021) indicated that the use of various calculation methods may result in approximately 7% underestimation of road CO 2 emission results when testing LPG-powered vehicles. This was also confirmed by Gis et al [34] (2021), indicating that the interchangeable treatment of indicators (dilution ratio and dilution factor) in mathematical calculations of exhaust emissions affected the measurement error of CO 2 concentration by 0.4%, CO by a maximum of 4%, and NO x by 1%.…”
Section: Literature Reviewmentioning
confidence: 99%